Association of Negative Symptoms of Schizophrenia Assessed by the BNSS and SNS Scales With Neuropsychological Performance: A Gender Effect - Wójciak, Paweł; Domowicz, Klaudia; Zabłocka, Marta; Michalak, Michał; Rybakowski, Janusz K. (Frontiers in Psychiatry, 2021)
Objective: The relationship between negative symptoms and neurocognitive performance in schizophrenia is well documented, but the mechanism of these connections remains unclear. The study aims to measure the relationship between the results on the new scales for the assessment of negative symptoms such as Brief Negative Symptom Scale (BNSS) and Self-evaluation of Negative Symptoms (SNS), and the results of some neurocognition tests. The second aim is to assess a possible gender effect on these associations. Methods: The study included 80 patients (40 men, 40 women) with schizophrenia, aged 19–63 (mean 38 years), during the improvement period (total PANSS score <80, unchanged pharmacological treatment in the last 3 weeks). They were assessed using the BNSS, SNS, Personal and Social Performance (PSP) scales, and the tests for neuropsychological performance such as the Trail Making Test (TMT-A, TMT-B), Stroop Color-Word Interference Test, Verbal fluency tests (VFT), Category fluency test (CFT), and Digit Symbol Substitution Test (DSST). Results: Male patients obtained higher scores than females on some PANSS and BNSS items. No gender differences were observed for the SNS scale. Female patients scored better in the PSP and CFT. In male patients, a significant positive correlation between the intensity of negative symptoms measured by the BNSS and the results of PSP with the Trail Making Test was observed. In female patients, we found a positive correlation between the results of BNSS and PSP with the Stroop Color-Word Interference Test. Conclusion: The obtained results confirm the relationship between negative symptoms and neurocognition in schizophrenia patients. However, in male and female patients such association was observed for different cognitive domains. Further research is needed to explain the nature of these differences.